2015
DOI: 10.1519/jsc.0000000000001110
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations to Short, Frequent Sessions of Endurance and Strength Training Are Similar to Longer, Less Frequent Exercise Sessions When the Total Volume Is the Same

Abstract: The hypothesis that the distribution of weekly training across several short sessions, as opposed to fewer longer sessions, enhances maximal strength gain without compromising maximal oxygen uptake was evaluated. Twenty-nine subjects completed an 8-week controlled parallel-group training intervention. One group ("micro training" [MI]: n = 21) performed nine 15-minute training sessions weekly, whereas a second group ("classical training" [CL]: n = 8) completed exactly the same training on a weekly basis but as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 19 publications
1
31
0
2
Order By: Relevance
“…The improvement in maximal aerobic capacity was around 20% in all groups. Kilen et al 19 studied training adaptations of professional soldiers in two training groups: one performing nine 15-min training sessions per week ("microtraining") and the other performing three 45-min sessions ("traditional training") during 8 weeks with sessions of strength, high-intensity endurance training and muscle endurance. Both groups improved shuttle run performance but only the "microtraining" group improved peak oxygen uptake, grip strength, and loaded lunge performance.…”
Section: Endurance Trainingmentioning
confidence: 99%
“…The improvement in maximal aerobic capacity was around 20% in all groups. Kilen et al 19 studied training adaptations of professional soldiers in two training groups: one performing nine 15-min training sessions per week ("microtraining") and the other performing three 45-min sessions ("traditional training") during 8 weeks with sessions of strength, high-intensity endurance training and muscle endurance. Both groups improved shuttle run performance but only the "microtraining" group improved peak oxygen uptake, grip strength, and loaded lunge performance.…”
Section: Endurance Trainingmentioning
confidence: 99%
“…Training frequencies can be interpreted across the whole spectrum, with some sports considering a 'high' frequency to be the equivalent of a 'low' frequency in other sports; for example, within basketball, the majority of the season is spent playing three games per week, whereby one or two dedicated RT sessions would be considered high frequency, compared to a sport such as rugby or American Football whereby that same frequency would be considered low. From a research perspective, there is also no clear definition of what constitutes high and low frequencies, with some studies for example labeling three sessions a week as low [28,29] frequency and some as high [30][31][32][33]. The authors, therefore, have not definitively classified any frequency as either being low or high but made comparisons as lower and higher.…”
Section: Analysis and Interpretation Of Resultsmentioning
confidence: 99%
“…Figure 1 illustrates that of the total studies identified, 142 articles were duplicates and, therefore, removed first. Following the application of the predetermined inclusion/exclusion criteria to both titles and abstracts of the identified studies, and with further inspection of the full text if required, a total of ten studies remained for further analysis [28][29][30][31][32][33][34][35][36][37].…”
Section: Search Resultsmentioning
confidence: 99%
“…The dominant arm was supported at shoulder height and fixed with the forearm supinated and the elbow angle at 90°, in a custom-made apparatus coupled to a strain gauge load cell (Tedea-Huntleigh Model No. 615, 2006, Herzliya Pituach, Israel;Kilen et al, 2015). The subjects performed 3 × 5-s maximal contractions interspersed with 55 s rest.…”
Section: One-arm Isometric Elbow Flexion Testmentioning
confidence: 99%